Geochronological and Paleomagnetic Constraints on the Lower Cretaceous Dalazi Formation from the Yanji Basin, NE China, and its Tectonic Implication - Zhongshan Shen (Minerals, 2021)
The Lower Cretaceous Dalazi Formation in the Yanji Basin, eastern Jilin Province is of particular interest because it contains key fresh water fossil taxa, oil and gas resources, a potential terrestrial Albian–Cenomanian boundary, and regional unconformities. However, the lack of a precise chronology for the non-marine strata has precluded a better understanding of the regional stratigraphic correlation and terrestrial processes. Here, we report magnetostratigraphic and U–Pb geochronologic results of a sedimentary sequence from the Xing’antun section in the Yanji Basin. Thirty-two zircons from the tuff sample were analyzed by secondary ion mass spectrometry (SIMS); the U–Pb zircon dating method yielded a weighted mean of 206Pb/238U age of 105.7 ± 0.8 Ma (2σ, internal error). Paleomagnetic results show that the Dalazi Formation is of normal polarity, which was correlated to the early chron C34n constrained by the SIMS U–Pb zircon geochronologic data, further demonstrating that the terrestrial sedimentary sequence of the upper Dalazi Formation is of late Albian age. The established geochronologic framework allows the regional correlation of the Dalazi Formation in the Yanji Basin to the strata from other terrestrial sequences in northeastern China. The similar geodynamic and geologic background between the Yanji Basin and other terrestrial rift basins in northeastern China suggests that the unconformity between the Dalazi and Longjing formations may represent syn-rift and post-rift stages in the Yanji Basin, and thus the switch from extension to contraction during the mid-Cretaceous, precisely constrained to ~106–101 Ma based on our new chronology and previously published high-precision U–Pb dating of the lower Longjing Formation. It is most likely attributable to the docking of the west Pacific plate along the East Asian continental margin.